Editorial (Shimmering Words: Research and Pedagogy E-Journal, 2020)
During the 21st century teachers and students have been witnesses of the unavoidable inclusion of the technology in education, specifically in the teaching-learning instruction, thus, the TIC (Technology of the information and communication), LKT (Learning and Knowledge Technologies), and TEP (Technologies for Empowerment and Participation) are used to support and strengthen the pedagogies in all areas of knowledge.Learning to learn in the digital age and the use of learning technologies are the new trends students and teachers are living; as a mandatory approach, nowadays education must be involved in the emerging pedagogies which are focused to encourage students and teachers’ interaction by means of technology, thus, the connection between theory and practice is done through the mediation of technological tools which also represent the management of knowledge in modern times.In the field of languages acquisition, these tools have become an opportunity to improve the use of foreign languages, especially because the class time is not enough to foster students’ communication skills; hence, technology is important in order to support and motivate students´ autonomous work; in our context, this is a way students acquire the necessary expertise to communicate with property in different settings.In addition to the immediate communication, further reading and research are ways to build students’ knowledge; besides, teachers have the possibility to offer students an extensive bibliography and academic resources that not only support students’ language learning but about topics of their own field of study according to their interests and learning needs; besides, it can be reinforced by the databases which are rich in the latest materials that are usually written in the original language (English, French, Chinese, Mandarin, Italian, Spanish, etc.), so students can consult in the original source and practice the foreign language.Finally, the use of technologies in education as well as in language acquisitions, represent meaningful strategies teachers and students must use to encourage the teaching and learning processes, they contribute to build knowledge and develop other skills necessary for current productivity such as team work, autonomy, information management, communication, languages proficiency, among others.
Keywords: inclusion of the technology in education